The Use of Thermography in Evaluation of Surgical Wounds in Small Animal Practice - Gumpert Herlofson, Erica (SLU/Dept. of Clinical Sciences (until 231231), 2017)
The aim of this study was to test the usefulness of thermal imaging in a clinical setting as a part of wound healing evaluation after surgical procedures. Forty-one client owned dogs and cats (thirty nine dogs and two cats) were included in the study which was a part of another study investigating the effects of local anaesthetics on wound healing. Thermal imaging and clinical assessment of the wound area was performed approximately fourteen days after surgical intervention. Clinical assessment was focused on evaluating wounds for signs of inflammation and thermal interpretation investigated if there was a significant difference in temperature between wound area and control area. The skin temperature in the wound area had a significantly lower temperature than control areas. Comparison of results from thermal image interpretation for correlation with clinical assessment of wound area had no statistical significance. The controversial finding of a malignant tumour being depicted as colder than surrounding tissue instead of warmer, which is described in the literature, illustrates the need for further research to improve thermal imaging diagnostic outcome in the oncology field. A potentially useful area for thermal imaging in every day clinical practice may lie in monitoring the healing of bone fractures but further studies are needed. The conclusion from this study was that subjective clinical evaluations of surgical wounds two weeks post surgery provides enough information for clinical decision making and thermal imaging is superfluous in this context. The method should be evaluated within the timeframe of the inflammatory phase to further explore its potentials in wound healing evaluation.